Bella Moth, Rattlebox Moth, Inornate Moth or Calico Moth, Utetheisa ornatrix (Linnaeus) (Insecta: Lepidoptera: Arctiidae: Arctiinae) - Donald W. Hall (EDIS)
The bella moth, Utetheisa ornatrix (Linnaeus), is one of our most beautiful moths. Unlike most moths, which are nocturnal, the bella moth is diurnal and flies readily when disturbed. Therefore, it is more commonly seen than nocturnal species by the general public. This document is EENY-358 (IN644), one of a series of Featured Creatures from the Entomology and Nematology Department, UF/IFAS Extension. Original publication date October 2005.